2018
DOI: 10.21608/ejbo.2018.3540.1168
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination of rigid ryegrass (Lolium rigidum) and sterile oat (Avena sterilis) under water salinity conditions at constant or alternating temperatures

Abstract: R IGID ryegrass (Lolium rigidum) and sterile oat (Avena sterilis) are well known grasses in many parts of the world. They grow in both grasslands and arable habitats and both are recorded as serious weeds of arable lands in many countries worldwide. Seed germination of both species was tested against four levels of water salinity (0, 100, 300, 500mM/L of NaCl) and five different temperature regimes, constant at 8°C or alternating temperatures at 6/14, 8/16, 10/18 and 10/20°C, all in dark/light photoperiods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…[13,27,28] studies about P. turgidum, Leymus chinensis and Lolium multiflorum noted similar trends with this study. Previous studies have shown there is usually a negative correlation between salt tolerance and germination percentage in Lolium species [29,30,31]. Germination energy, which is called the first few days of the germination stage, in higher temperature affects more negatively than salt levels in this study.…”
Section: Discussionmentioning
confidence: 62%
“…[13,27,28] studies about P. turgidum, Leymus chinensis and Lolium multiflorum noted similar trends with this study. Previous studies have shown there is usually a negative correlation between salt tolerance and germination percentage in Lolium species [29,30,31]. Germination energy, which is called the first few days of the germination stage, in higher temperature affects more negatively than salt levels in this study.…”
Section: Discussionmentioning
confidence: 62%